A review on anticancer and biochemical properties of Clinacanthus nutans - Zakaria, Khairun Najwa; Amid, Azura (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Clinacanthus nutans (CN) (Belalai Gajah in Malay) is often used as herbal remedies complementary. The extracts from its dried leaves has been used traditionally to treat disease such as anti-venom for snake/insect bite. Phytochemical screening showed that the extract comprises of lupeol,  –sitosterol, stigmasterol, Botulin, myricyl alcohol C-glycosyl flavones (vitexin, isovitexin, shaftoside, isomollupentin 7-O-b -glucopyranoside, orientin and isoorientin), sulfur-containing glucosides, cerebrosides mixer, a monoacylmonogalactosylglycerol, 13-hydroxy-(13-S)-phaeophytin b, Pupurin-18-phytyl ester, phaeophorbide and chlorophyll derivatives. Literature search showed that the ethanolic extract of CN had an antioxidant activity and protective effect against free radical. Experimental evidences confirmed that the CN could be used in treating tumor and cancer since it showed anticancer and antiproliferative properties. Its petroleum ether extracts also demonstrated the strongest cytotoxic activity against HeLa and K-562 cells. The bioactive compounds from CN are potential cytotoxic, antioxidant and antiproliferative properties against cultured cancer cell lines, suggesting an alternate adjunctive regimen for cancer prevention or treatment.